Using a multi-layer Lagrangian inverse analysis to study CO2 isotope exchange in plant canopies - Santos, Marshall Victor Chagas (2019)
Stable isotopes of CO2 are useful to study biosphere-atmosphere exchange processes. Recent advances in optical based isotope techniques has provided high-temporal resolution and accurate isotope measurements suitable for ecosystem scale studies. These novel measuring techniques can be combined with micrometeorological approaches, such as multi-layer Lagrangian models, to study CO2 isotope exchange in plant canopies. The main objectives of this study were: 1) to evaluate the feasibility of the localized near-field theory (LNF) to study 13CO2 and C18OO isotope exchange in different plant canopies; 2) to examine the LNF theory as an independent non-isotopic method to estimate separately the net-photosynthesis (FA) and non-foliar respiration (FR) in a corn canopy; and 3) to evaluate whether direct half-hourly estimates of isotope compositions of net CO2 ( N), canopy ( P) and below-canopy ( R) fluxes from LNF could be used in a isotope based partitioning approach (IFP method) to partition NEE measurements. Concentration of stable isotopes of CO 2 were measured within and above a temperate deciduous forest, tallgrass prairie and corn field using a multi- port sampling system and the tunable diode laser spectroscopy (TDLAS) technique. An EC system was also used to measure the wind velocity and the net CO 2 fluxes (NEE) above the canopies. The performance assessment of LNF on estimating isotope exchange within different plant canopies and to partitioning NEE in a corn canopy included direct comparisons with the traditional isotope flux ratio (IFR) method and a night-time based flux partitioning (RP) approach, respectively. Changes in CO2 storage were used to investigate the degree of decoupling between below and above- canopy airflows. Results showed that the LNF estimates of NEE and isotope CO2 exchange for the forest canopy were greatly affected by the flux decoupling. However, the LNF theory was shown to be suitable within well-mixed short canopies, where changes in CO2 storage were small. The magnitude of CO2 concentration gradients had great impact on both IFR and LNF N estimates. Nevertheless, the LNF theory reduced roughly 74% the uncertainties of IFR method. For the non-isotope partitioning, The LNF FA estimates captured the expected seasonal canopy physiological variation better than RP. Large uncertainties in LNF FR estimates were observed when the canopy was fully developed under low turbulent mixing periods. For the isotope-derived partitioning, the IFP method was highly sensitive to the Deq, where large uncertainties were found when Deq < 3 Å. However, a considerable reduction in the uncertainties and more realistic flux estimates were observed when weak Deq (< 3 Å) periods was filtered out from IFP predictions. Overall, these results suggests that LNF theory can be successfully used to study isotope exchange and partitioning NEE in well-mixed plant canopies. However, further studies are still needed to quantify the random and systematic errors associated with LNF predictions.